Precariousness and Quality of Life—a Qualitative Perspective on Quality of Life of Households in Precarious Prosperity in Switzerland and Spain - Budowski, Monica; Schief, Sebastian M.; Sieber, Rebekka (My University, 2015)
Households’ resources and constraints are key components of quality of life (QOL). QOL also depends on how these are evaluated. In times of crisis one expects subjective wellbeing and quality of life to decline. We argue that the quality of life depends on objective living conditions, their subjective evaluation and the ability to maintain or improve the situation of “embedded individuals”. This ability, in turn, depends on the opportunities provided by the state, labour markets, families and communities. We analyse qualitative interviews (2008–2010) with around 25 households in precarious prosperity in two cities (Pamplona, Spain and Lausanne, Switzerland) to elaborate their QOL. Few sampled Swiss households witnessed a decline in socio-economic status, contrary to the Spanish. Domains important to these households for QOL varied according to the opportunity structures: in the Spanish sample QOL was related to the opportunities for income, work, and security to plan ahead; in the Swiss sample to health, work-life balance and loneliness. In both samples, QOL varied according to scope of agency, people’s position within the life course, the households’ past experiences, current situation and future perspectives. Lack of future perspectives and opportunities lowered QOL; reframing, adaption and accepting the situation sometimes moderated QOL. We conclude that apart from living conditions and/or subjective wellbeing, households’ agency within opportunity structures is a promising direction for further research in QOL.
Keywords: Precarious prosperity; Quality of life; Spain; Switzerland; Scope of agency